Is There a Relation between Hypothyroidism and Polycystic Ovary Syndrome and its Metabolic Components? - Bonakdaran, Shokoufeh; Milani, Nasrin; Khorasani, Zahra M.; Hosseinzadeh, Mansoore; Kabiri, Mona (Current Diabetes Reviews, 2023)
Background: Polycystic Ovary Syndrome (PCOS) is one of the most prevalent endocrine illnesses among women of reproductive age. PCOS is linked to several issues, including hypothyroidism and metabolic disorders. Hypothyroidism seems to be associated with insulin resistance and other metabolic factors. Objective: The present study aimed to evaluate the incidence of hypothyroidism in PCOS patients and compare it with healthy controls. Moreover, the impact of hypothyroidism on metabolic parameters, particularly insulin resistance, in PCOS patients was also examined. Methods: This study was conducted on 41 women with PCOS and 41 healthy women as controls from March to November, 2018. Participants' demographic information was recorded. Thyroid function tests were compared between the case and control groups. Metabolic parameters were examined between hypothyroid and euthyroid PCOS individuals. Results: Patients with PCOS displayed a greater incidence of hypothyroidism and a higher level of anti-thyroid peroxidase antibodies compared to the control group. High-density lipoprotein (HDL) cholesterol was substantially higher in hypothyroid PCOS patients than in non-hypothyroid individuals, although no significant changes were observed in other metabolic markers. Hypothyroid PCOS patients and those without hypothyroidism did not differ in insulin resistance. Autoimmunity was not found to be linked to a higher risk of metabolic problems. Conclusion: As evidenced by the results of this study, PCOS patients had a higher prevalence of subclinical hypothyroidism than healthy subjects. Metabolic indicators, except for HDL, were not different between PCOS patients with and without hypothyroidism.
Keywords: hypothyroidism